Pneumothorax, pneumomediastinum and subcutaneous emphysema as respiratory complications of COVID-19 - Rawal, Prabhat; Shrestha, Surendra Man; Gurung, Anju; Poudel, Dipesh (Journal of Nepal Health Research Council, 2024)
Background: Pneumothorax, pneumomediastinum and subcutaneous emphysema are respiratory complications of Coronavirus disease 2019 occurring with noteworthy frequency in patients especially with severe disease. They can be life-threatening and often complicate patient managment.Methods: This was a retrospective, observational study of patients admitted in Nepal Armed Police Force hospital from 13/05/2020 to 28/12/2021 diagnosed with pneumothorax, pneumomediastinum or subcutaneous emphysema singly or in combination. Data were collected from clinical charts, imaging records and electronic medical records of Severe Acute Respiratory Syndrome Coronavirus-type 2 positive patients 18 years and older. The frequency and type of the defined complications, the inflammatory markers and ventilatory parameters just prior to their diagnosis, the duration of hospitalization and ICU admission and in-hospital mortality rate were studied. Results: Out of 4013 COVID-19 patients admitted in the hospital during the period, a total of 28 patients were observed to develop the complications, the overall incidence being 0.7% among hospitalized patients and 5.6% among ICU patients. The proportion of subcutaneous emphysema (64.3%) was highest followed by pneumomediastinum (46.4%) and then pneumothorax (39.3%) existing singly or in combination among the 28 patients, where four patients developed the complications spontaneously. Mean Positive End Expiratory Pressure of 12.1±2.6 cmH2O and Peak Inspiratory Pressure or Pressure Support of 30.9±10.3 cmH2O were observed for patients under positive pressure ventilation. Most of the patients who developed the complications (78.6%) died during treatment.Conclusions: Pulmonary air leak complications occur frequently in COVID-19 patients treated with or without positive pressure ventilation signifying increased disease severity, risk of ICU admission and high mortality rate. Hence, clinicians should be vigilant of these complications in all patients affected with COVID-19 and institute timely management. Keywords: Barotrauma; COVID-19; incidence; pneumomediastinum; pneumothorax.